Mekanisme Koordinasi antara Dinas Sosial, Dinas Kesehatan, dan Satuan Polisi Pamong Praja (Satpol PP) dalam Penanganan ODGJ (Orang dengan Gangguan Jiwa) di Kota Solok - Nilam Akhsanul Husna; Siska Sasmita (MASALIQ, 2025)
The importance of cross-sectoral coordination in the management of Orang Dengan Gangguan Jiwa (ODGJ, or People with Mental Disorders) forms the background of this study, particularly in the city of Solok, which faces coordination challenges despite the Social Services Office, Health Office, and Civil Service Police Unit (Satpol PP) each having their own operational guidelines. The response remains largely reactive and fragmented due to the absence of an integrated Standard Operating Procedure (SOP), differing institutional priorities, and limited facilities. This study aims to analyze the forms of inter-agency coordination in handling ODGJ cases and to assess their effectiveness based on Hasibuan’s coordination factor theory and Mintzberg’s coordination mechanisms. A descriptive qualitative approach was employed through in-depth interviews, field observations, and document analysis involving relevant agencies in Solok. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that inter-agency coordination has occurred through informal communication, limited supervision, and internal SOPs; however, it remains ineffective due to the lack of formal unified actions, underdeveloped communication structures, inconsistent division of labor, and weak cross-sectoral discipline. The application of coordination mechanisms such as mutual adjustment, direct supervision, and standardization remains partial and highly dependent on individual initiative in the field. The study concludes that improving coordination effectiveness requires specific regional regulations, integrated cross-sectoral SOPs, and ongoing joint training. These findings contribute to strengthening public service governance in mental health, particularly in local-level ODGJ management.